2016
DOI: 10.1037/men0000033
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of television use to beliefs about fathers and gendered family roles among first-time expectant parents.

Abstract: TV content has been documented to portray a limited range of gender roles, and to frequently depict fathers as incompetent parents. Accordingly, this study explored whether first-time expectant parents' beliefs about gendered family roles and the importance of fathers to child development were related to their TV use. Participants were 201 individuals (122 women, 79 men) from across the United States expecting their first biological child in a cohabiting heterosexual relationship. Participants completed an onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 54 publications
(66 reference statements)
0
8
0
1
Order By: Relevance
“…Given the potential of TV content to socialize viewers (Bandura, 2001; Gerbner & Gross, 1976; Morgan, 2009), particularly regarding masculine gender roles and norms (Giaccardi et al, 2016; Kuo & Ward, 2016; Scharrer & Blackburn, 2018), the depictions of sitcom fathers are important to understand. From the present study, it appears that, over time, viewers of U.S. family sitcoms increasingly received a message that positions fathers as relatively uninvolved in giving out advice, rules, or discipline to children, and when they do engage in these parenting interactions, they increasingly do so in a foolish and incompetent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the potential of TV content to socialize viewers (Bandura, 2001; Gerbner & Gross, 1976; Morgan, 2009), particularly regarding masculine gender roles and norms (Giaccardi et al, 2016; Kuo & Ward, 2016; Scharrer & Blackburn, 2018), the depictions of sitcom fathers are important to understand. From the present study, it appears that, over time, viewers of U.S. family sitcoms increasingly received a message that positions fathers as relatively uninvolved in giving out advice, rules, or discipline to children, and when they do engage in these parenting interactions, they increasingly do so in a foolish and incompetent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Both cultivation theory and social–cognitive theory have been used to explain TV’s role in shaping understandings of and conformity with gender roles and norms (Dill & Thill, 2007; Sink & Mastro, 2017). In fact, Kuo and Ward (2016) found that exposure to televised portrayals of incompetent fathers was correlated with holding less egalitarian beliefs about gender roles within a sample of heterosexual couples expecting their first child; depictions of fathers may have important real-world effects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Greenberg and colleagues found that heavy viewers were more likely to form the belief that real-world families show greater support and concern for one another. A more recent study examined beliefs about fathers, gendered roles, and television viewing habits among first-time expectant parents (Kuo and Ward 2016). Results suggested that an increased attribution of realism to televised content predicted belief in gendered family roles; additionally, heavy television viewers were more likely to downplay the role of the father as it relates to a child's development.…”
Section: Related Media Effects Theories: Cultivation Analysis and Socmentioning
confidence: 99%
“…The print and TV media seem to have no such agenda when it comes to the portrayal of fathers (Kuo and Ward, 2016;Wadsworth, 2015 andEvans, 2015) with father figures on television, (Kuo and Ward, 2016), print (Evans, 2015) and in family films (Wadsworth, 2015). In Kuo and Ward's study of 201 men and women in the United States, they concluded that TV content reinforced traditional gendered family role beliefs about mothers being more important to child development.…”
Section: 5: Microsystem and Mesosystem -School And Homementioning
confidence: 99%
“…Teacher-mothers construct images of what they perceive to be the expectations of society (Knowles et al, 2009), and whilst Aliyah describes her need to do some things for herself, she also describes this as selfish. The position taken is that she is being unkind or unfair in her attempt to have some time for herself and this is a worrying discourse -one that is not replicated in media portrayals of fatherhood (Evans, 2015;Kuo and Ward, 2016;Wadsworth, 2015).…”
Section: 4: Exosystem: Part-time Work As Panaceamentioning
confidence: 99%